1992
DOI: 10.1093/mutage/7.4.265
|View full text |Cite
|
Sign up to set email alerts
|

A Chinese hamster ovary cell mutant (EM-C11) with sensitivity to simple alkylating agents and a very high level of sister chromatid exchanges

Abstract: We have isolated a Chinese hamster ovary cell mutant hypersensitive to monofunctional alkylating agents. The mutant, designed as EM-C11, showed hypersensitivity to ethyl methanesulfonate (EMS), methyl methanesulfonate and ethylnitrosourea (8-, 7- and 2-fold, respectively, based on D10 values). About 2-fold increased sensitivity towards 4-nitroquinoline-1-oxide and only slightly increased sensitivity to X-rays (1.4-fold) and mitomycin C treatment (1.6-fold) were found in this mutant. EM-C11 was not hypersensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
69
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 0 publications
5
69
0
Order By: Relevance
“…In this work, we have demonstrated that XRCC1 is physically associated with PARP in vivo and in vitro. The DNA repair factor XRCC1 complements the CHO cell lines EM9 and EM-C11, which are hypersensitive to both monofunctional alkylating agents and ␥ rays (50,51,58). In response to genotoxic agents that induce DNA base damage, EM9 and EM-C11 exhibit 10-fold increases in the occurrence of sister chromatid exchanges and severe defects in the rejoining of DNA breaks (19,31,58).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we have demonstrated that XRCC1 is physically associated with PARP in vivo and in vitro. The DNA repair factor XRCC1 complements the CHO cell lines EM9 and EM-C11, which are hypersensitive to both monofunctional alkylating agents and ␥ rays (50,51,58). In response to genotoxic agents that induce DNA base damage, EM9 and EM-C11 exhibit 10-fold increases in the occurrence of sister chromatid exchanges and severe defects in the rejoining of DNA breaks (19,31,58).…”
Section: Discussionmentioning
confidence: 99%
“…The DNA repair factor XRCC1 complements the CHO cell lines EM9 and EM-C11, which are hypersensitive to both monofunctional alkylating agents and ␥ rays (50,51,58). In response to genotoxic agents that induce DNA base damage, EM9 and EM-C11 exhibit 10-fold increases in the occurrence of sister chromatid exchanges and severe defects in the rejoining of DNA breaks (19,31,58). Consistent with its proposed role in mammalian BER, XRCC1, which has no demonstrated catalytic activity, is supposed to serve as a scaffold protein during the BER reaction through its interaction with DNA ligase III (7,25,37) and DNA polymerase ␤ (25).…”
Section: Discussionmentioning
confidence: 99%
“…Zdzienicka, Department of Molecular Cell Genetics, Collegium Medicum in Bydgoszcz, Nicolaus-Copernicus University in Torun (Bydgoszcz, Poland; ref. 25,26). Cells were grown in Ham F-10 media (supplemented with 10% FBS and 1% penicillin/streptomycin; PAA).…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…49 Wild-type CHO-9 and mutants originating from it are XR-C1-defective for DNA-PK, 50 43-3B defective for ERCC1, which is involved in nucleotide excision repair, 51 and EM-C11 defective for XRCC1 involved in base excision repair. 52 The hamster cells were cultured in RPMI-1640 (Life Technologies) supplemented with 10% fetal bovine serum (PAA Laboratories) and penicillin/streptomycin and incubated at 37°C in a humidified atmosphere with 7% CO2. Geneticin (G418 sulfate) was added at a concentration of 500 μg/ ml to cell cultures of V-C8mBAC, VC8+MGMT, Irs1-SF+MGMT, V3 and V3-WT cells.…”
mentioning
confidence: 99%